2016
DOI: 10.2298/sarh1602116b
|View full text |Cite
|
Sign up to set email alerts
|

How can eHealth enhance adherence to cancer therapy and supportive care?

Abstract: eHealth is currently a hot topic, but is certainly not a new one. The use of communications technology to relay health-related information or provide medical services has been around since the advent of this technology. It has been primarily over the last decade that eHealth has seen a global expansion, due to the far-reaching capabilities of the Internet and the widespread use of wireless technology. This paper will outline what eHealth is, what adherence is, and how eHealth can help with adherence, in cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…We also found that approximately 89% of the participants would like to revisit the Department of Guangdong Online Hospital. The number of participants who reported complete adherence to physician’s advice was almost equal to that of those reporting partial compliance and no compliance, which was consistent with Bateman’s research [28]. The findings of our study indicated that telemedicine was popular but did not have a good compliance.…”
Section: Discussionsupporting
confidence: 90%
“…We also found that approximately 89% of the participants would like to revisit the Department of Guangdong Online Hospital. The number of participants who reported complete adherence to physician’s advice was almost equal to that of those reporting partial compliance and no compliance, which was consistent with Bateman’s research [28]. The findings of our study indicated that telemedicine was popular but did not have a good compliance.…”
Section: Discussionsupporting
confidence: 90%
“…These challenges include demographic changes with more elderly patients living with chronic conditions and long distances to hospitals [11,13-16]. In cancer care, the use of telehealth has, as mentioned above, shown beneficial aspects not only as support interventions for relatives but also as a positive addition to promote adherence in treatment and care, improving patient outcomes [17,18]. In spite of these experiences using telehealth, numerous barriers must be considered if the implementation is to succeed [14].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that patients’ engagement with e-monitoring leads to good adherence of instructions 5,6. A mobile application (app) for healthcare is a tool that can improve patients’ engagement in self-care, and can be helpful for behavioral adherence 7,8. The versatility of mobile apps makes users more participatory, thus empowering them in making an informed choice for themselves 9.…”
Section: Introductionmentioning
confidence: 99%
“…Mobile apps is one of the healthcare services that has promotes patients’ health and has positive effects on their behavioral adherence. Mobile apps are used to support patients’ behavioral adherence, such as in the cases of chronic kidney disease, chronic obstructive pulmonary disease, heart failure, diabetes, cancer, and post-operative management 7,10,11,1719. However, whether patients continue to use an app service depends on their satisfaction with the service 22,23.…”
Section: Introductionmentioning
confidence: 99%